PENERAPAN JARINGAN SARAF TIRUAN STANDARISASI HARGA BARANG DISTRIBUTOR DI MEDAN DENGAN ALGORITMA LAVENBERG MARQUARDT - Supriyanti Matanari; Rivalri Kristianto Hondro (STMIK Budi Darma, 2018)
The Medan Central Bureau of Statistics is tasked with surveying data or calculating quality statistical data and information which includes accuracy of relevance and also for price standardization or determination. The problem in setting the price standard is because many companies raise prices without surveying data first and some other companies do not adjust the price of one to another. To handle this, one method is needed to study and analyze Distributor Item Price data to be uniform, using knowledge of artificial neural network analysis using the Levenberg-Marquardt method. With this activity the Medan Central Bureau of Statistics hopes that the company in an effort to increase customer satisfaction with the products produced can be done by producing a product or item with high quality and quality with balanced pricing in accordance with the conditions in the market (adjusted to community income). The results obtained through this study are the uniformity of the prices of distributor goods in the market, which have previously been through the process of testing and applying mathematically statistically using matlab software.Keywords: Artificial Neural Networks, Levenberg-Marquardt Method, Distributor Prices, MATLAB